2012
DOI: 10.1016/j.jcrs.2012.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of corneal aberrations on intraocular lens power calculations

Abstract: Mrs. Canovas and Dr. Artal hold a provisional patent application on the ray-tracing procedure. Mrs. Canovas is an employee of Abbott Medical Optics Groningen B.V. No other author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…This assumption yields accurate values in normal regular corneas with minimal variations in anteroposterior corneal curvature, which was proven by ray-tracing studies. [14] Nonetheless, scarred corneas with irregular surface exhibit abnormal anteroposterior corneal curvature relation, violating the hypotheses allowing intraocular lens power calculation relying on Keratometry. Furthermore, the accuracy of measurements is frequently hindered in such irregular corneas, usually encountered after corneal refractive procedures, corneal ectasia, scarred corneas, or xerophthalmia.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption yields accurate values in normal regular corneas with minimal variations in anteroposterior corneal curvature, which was proven by ray-tracing studies. [14] Nonetheless, scarred corneas with irregular surface exhibit abnormal anteroposterior corneal curvature relation, violating the hypotheses allowing intraocular lens power calculation relying on Keratometry. Furthermore, the accuracy of measurements is frequently hindered in such irregular corneas, usually encountered after corneal refractive procedures, corneal ectasia, scarred corneas, or xerophthalmia.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption yields accurate values in normal regular corneas with minimal variations in anteroposterior corneal curvature, which was proven by ray-tracing studies. [14] Nonetheless, scarred corneas with irregular surface exhibit abnormal anteroposterior corneal curvature relation, violating the hypotheses allowing intraocular lens power calculation relying on Keratometry. Furthermore, the accuracy of measurements is frequently hindered in such irregular corneas, usually encountered after corneal refractive procedures, corneal ectasia, scarred corneas, or…”
Section: Discussionmentioning
confidence: 99%
“…reflecting the amount of myopic correction 6,8,9 . Canovas et al 12 demonstrated that the incorporation of corneal spherical aberration at 4.0 mm was important for improving accuracy in prediction of IOL power. Mori et al 11 concluded that both Q-value and spherical aberration showed statistically significant correlations with refractive error.…”
Section: Discussionmentioning
confidence: 99%
“…Another study concluded that corneal asphericity on the anterior surface influenced the refractive outcomes calculated by the SRK/T formula in the eyes with a prior myopic LASIK history 11 . Considering corneal spherical aberration also improved the predictability of refractive outcomes in post-LASIK eyes when the ray tracing prediction was applied 12 .…”
mentioning
confidence: 99%